#TITLE_ALTERNATIVE# - PRASSETIO (NIM : 12212040),
In wells that use aritificial lift with pumps method, such as ESPs, SRPs, and PCPs, fluid level must be maintained above the pump suction. If the well produces gas, gas will flow through casing annulus after it was liberated from oil phase. As the production goes on, more amount of gas is accumulated in the casing annulus resulting in casing pressure buildup. If no action taken to handle the situation, the casing pressure will push the fluid level down. In the worst case, the fluid level reaches below pump setting depth, thus the pump cannot operate anymore. So, the gas accumulated in casing annulus must be removed frequently. With the existing environmental restriction to vent the gas to the atmosphere, gas will be vented to or produced through the flowline. In this study, the gas will be vented to the oil flowline frequently. Casing annulus and the flowline are connected with a pipe equipped with a valve. This valve will open when the gas column pressure in the casing annulus is higher than the wellhead pressure. The gas column pressure buildup with time will be modeled to predict when the valve should be opened and how long the gas venting process will take time. Sensitivity analisys is also conducted to determine the effect of oil rate to the time when the valve should be opened and when the valve will be closed